A CROSS-CULTURAL STUDY OF REFUSAL STRATEGIES OF AMERICAN AND ARMENIAN ENGLISH SPEAKERS - Hovsepyan, Gohar (Armenian Folia Anglistika, 2021)
Several studies have been carried out on refusal strategies that native and non-native English speakers employ to mitigate potential threat to listener’s face when forming refusals to various speech acts, such as requests, offers, invitations, etc. This study adds the perspective of Armenian English speakers in using such mitigation strategies. The objective of the study is to identify similarities and differences in the use of various politeness strategies used in refusal acts by native English speakers (NES) and Armenian non-native English speakers (ANNES) with the aim of establishing the extent of cultural impact on pragmatic competence of ANNES. Language data was collected among 24 Armenian English speakers of high level of English proficiency and 15 American English speakers. A modified version of the Discourse Completion Test (DCT) developed by Beebe, Takahashi, and Uliss-Weltz (Beebe et al., 1990) was used to collect data. Along with considerable similarities in the use of politeness strategies in refusals between the two groups which indicate the high degree of pragmatic competence of ANNES, the analysis of the data also revealed some differences which attest to certain impact of the Armenian culture on this competence. The differences are mainly observed in frequency of use and in the content of the same strategies used by the two groups.